Effect of geometry on temporal development of quasi-1D jet scour - Tan, Ian Haoyang (2018)
The phenomenon of jet scouring has been studied extensively over the last 50 years with numerous experiments conducted in order to achieve a deeper understanding of the 3-dimensional (3D) and 2-dimensional (2D) scouring effect. However, the study of a 1-dimensional (1D) scouring effect is still relatively new because in the physical world, a 1D sand scouring effect with scour depth (ds) as the only changing variable does not truly exist. Nevertheless, by restricting the scour width (Ws) and scour length (Ls) to an infinitesimal scale, it is possible to simulate a quasi-1D jet scour scenario using a submerged impinging jet. The objective of this study was to obtain an improved understanding of scouring by conducting a study of the temporal development of a quasi-1D jet scour. Experimental dimensions such as sediment size (d50), impingement height of jet (H), mean jet velocity (U0) and scour bed length (L) were varied in order to examine their effect on scour development. Two different experimental set-ups were built in the hydraulics laboratory so that tests could be conducted to measure and obtain the necessary quasi-1D experimental data. The data were then analyzed in order to deduce the effect of various geometries on quasi-1D scouring. From the results, it was inferred that a quasi-1D scour follows an exponential development curve. This development curve comprises 4 main development phases which are consistent with the conventional 2D and 3D scour development phases (initiation phase, development phase, stabilization phase & equilibrium phase). It was discovered that quasi-1D equilibrium scour depth (dse) generally decreased when impingement height is increased, with the exception of a variation at H = 2.5 cm due to jet diffusion effect. It was also observed that both dse and time to reach equilibrium (te) increase when L was increased due to a larger erodible bed volume which facilitates better vortex formation. A quasi-1D jet scour was also found to achieve the equilibrium phase 90 times faster as compared to a 2D scour. Additionally, past researchers have derived a general form for pier scour equation. This equation was modified to relate changes in scour depth for the quasi-1D situation. Two equations were proposed: the first relating scour depth (ds) to impingement height (H), and the other relating ds to scour bed length (L). This study will allow us to achieve a better understanding of the scouring phenomenon by eventually comparing the nature of quasi-1D scouring with that of 2D and 3D scouring.